Gymnocalycium schroederianum subsp. boessii, subsp. nov. - Kiesling, Roberto (2002)
Gymnocalycium schroederianum subsp. boessii is described, and a determination key for thesubspecies is provided. Additionally refference of the types and synonyms of all the subspecies are given.